2005
DOI: 10.1007/s00246-005-0927-2
|View full text |Cite
|
Sign up to set email alerts
|

Successful One-Stage Repair of Unilateral Agenesis of Pulmonary Artery

Abstract: Unilateral agenesis of the pulmonary artery is a rare congenital anomaly that is commonly associated with ventricular septal defect (VSD). Its clinical presentation is diverse, and if left untreated, it can lead to significant damage and even death. Several surgical techniques have been developed for its management, with variable results. We report the case of a 2-month-old infant with agenesis of the left pulmonary artery (PA) and VSD. One-stage primary surgical re-anastomosis was successful in establishing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The choice of treatment is based on the symptoms of individual patients, PA anatomy and associated aortopulmonary collaterals, associated cardiovascular anomalies, and pulmonary hypertension 2 . An “ideal” surgical treatment for UAPA would achieve the restoration of antegrade blood flow in the ipsilateral lung and the repair of any congenital heart defects 9,10 . However, very few studies have reported on the treatment of UAPA, and selective pulmonary vein angiogram is not performed routinely to evaluate PA development 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The choice of treatment is based on the symptoms of individual patients, PA anatomy and associated aortopulmonary collaterals, associated cardiovascular anomalies, and pulmonary hypertension 2 . An “ideal” surgical treatment for UAPA would achieve the restoration of antegrade blood flow in the ipsilateral lung and the repair of any congenital heart defects 9,10 . However, very few studies have reported on the treatment of UAPA, and selective pulmonary vein angiogram is not performed routinely to evaluate PA development 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on a literature data analysis, we suggest the following classification of bi-pulmonary repair of UAPA associated with CHD. Group I: Single-stage operations with simultaneous repair of intracardiac defects and restoration of the antegrade blood flow in the ipsilateral lung: 8,1820 (a) Single-access technique (b) Double-access technique. Group II: Multi-stage operations with primary restoration of communication between the pulmonary trunk and the hilar artery: 8,12,17 First stage: (a) Restoration of the antegrade blood flow in the ipsilateral lung (b) Restoration of the antegrade blood flow in the ipsilateral lung in combination with a palliative operation: In combination with systemic-to-pulmonary shunt with the hilar artery In combination with systemic-to-pulmonary shunt with the contralateral pulmonary artery In combination with the reconstruction of the right ventricular inflow tract In combination with an endovascular procedure. Second stage: complete repair of intracardiac defects. Group III: Multi-stage operations with secondary restoration of communication between the pulmonary trunk and hilar artery: 8,12 First stage : palliative operation: (a) Systemic-to-pulmonary anastomosis with the hilar artery (b) Systemic-to-pulmonary anastomosis with the contralateral pulmonary artery (c) Reconstruction of the right ventricular inflow tract (d) Endovascular procedure. Second stage: restoration of the antegrade blood flow in the ipsilateral lung with simultaneous or postponed complete repair of intracardiac defects. Based on literature data as well as on our own experience, we believe that the algorithm in Figure 1 for surgical treatment in patients with UAPA and concomitant CHD is appropriate.
Figure 1.Algorithm of the preferred surgical treatment in patients with unilateral absence of a brunch pulmonary artery (UAPA) and concomitant congenital heart defects (CHD).
…”
Section: Discussionmentioning
confidence: 99%
“…Group I: Single-stage operations with simultaneous repair of intracardiac defects and restoration of the antegrade blood flow in the ipsilateral lung: 8,1820 (a) Single-access technique (b) Double-access technique. …”
Section: Discussionmentioning
confidence: 99%
“…The term isolated pulmonary artery of ductal origin (IPADO) is more appropriate as the native 6 th arch vessel is not absent [17, 27]. Review of published reports identified >160 cases of IPADO [10, 13, 21, 26, 29, 32]. Initially, patients with IPADO can remain asymptomatic for a long period, thus the diagnosis may not be made until adulthood [4].…”
Section: Introductionmentioning
confidence: 99%